PENGEMBANGAN BAHAN AJAR MAJALAH BERBASIS ANDROID PADA MATERI ADIKSIMBA BAHASA INDONESIA KELAS 4 SDN PURUT KOTA SERANG - Anna Qurrotul Ain; Dewi Sulastri; Lusi Aprilia; Ujang Jamaludin; Sigit Setiawan (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
ABSTRACTThe purpose of this study was to increase students' literacy interest andstudents' reading comprehension through the development of android magazineteaching materials on the ADIKSIMBA material for grade 4 Indonesian. Theresearch method used was R&D with the borg and gall model. Analysis of researchdata using the Likert and Guttman scales. The research subjects were taken from4th grade students at SDN Purut City of Serang. The results of the validationpercentage recapitulation research by getting a value of 84.5% means that thisteaching material is categorized as a very good teaching material and is veryfeasible to be tested on students and the initial test obtained an average score of57.5 and in the final test obtained an average score 83 concluded that the use ofteaching materials for this magazine can improve students' understanding ofinterrogative sentences using the ADIKSIMBA element. ABSTRAKTujuan pada penelitian ini adalah meningkatkan minat berliterasi siswa danpemahaman membaca siswa melalui pengembangan bahan ajar majalah androidpada materi ADIKSIMBA mata pelajaran Bahasa Indonesia kelas 4. Metodepenelitian yang digunakan adalah R&D dengan jenis model borg and gall. Analisisdata penelitian menggunakan skala likert dan guttman. Subjek penelitian diambildari siswa kelas 4 SDN Purut Kota Serang. Hasil penelitian rekapitulasi persentasivalidasi dengan mendapatkan nilai 84,5% artinya bahan ajar ini dikategorikansebagai bahan ajar yang sangat baik dan sangat layak untuk diujicobakan kepadasiswa dan tes awal didapatkan rata-rata nilai 57,5 dan pada tes akhir didapatkanrata-rata nilai 83 disimpulkan bahwa penggunaan bahan ajar majalah ini dapatmeningkatkan pemahaman siswa tentang kalimat tanya menggunakan unsurADIKSIMBA.